2018
DOI: 10.15520/ijcrr/2018/9/07/553
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Career Development and Organizational Culture to Employee Performance with Motivation of Work as Intervening Variable in Cooperation in Denpasar Village

Abstract: Research on career development and organizational culture on performance with work motivation as intervening variable is done at cooperative located in Pedungan village of South Denpasar Pedungan Village is a village located in South Denpasar District, Denpasar City, Bali Province. The development of cooperatives is currently supported by the development of small and medium enterprises (SMEs). The number of cooperatives in the village pedungan is 33 cooperatives with the total number of employees is 338 employ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
9
0
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 0 publications
6
9
0
9
Order By: Relevance
“…The findings of this study are supported by Wambugu (2014), Laras and Susanti (2021), Wardani et al, (2016), Nurvitasari et al, (2020), Arianty (2014), (Manggis et al, 2018), and Muis et al, (2018). According to their findings, organizational values had a significant impact on employee performance.…”
Section: The Impact Of Organizational Culture On Performancesupporting
confidence: 81%
See 1 more Smart Citation
“…The findings of this study are supported by Wambugu (2014), Laras and Susanti (2021), Wardani et al, (2016), Nurvitasari et al, (2020), Arianty (2014), (Manggis et al, 2018), and Muis et al, (2018). According to their findings, organizational values had a significant impact on employee performance.…”
Section: The Impact Of Organizational Culture On Performancesupporting
confidence: 81%
“…The research result confirmed a positive relationship between organizational culture and career development. Concerning this, employee career planning and development are inextricably linked to the company's organizational culture (Manggis et al, 2018).…”
Section: The Impact Of Organizational Culture On Career Developmentmentioning
confidence: 99%
“…Budaya organisasi adalah pola dasar yang diterima oleh organisasi untuk bertindak dan memecahkan masalah, membentuk karyawan yang mampu beradaptasi dengan lingkungan dan menyatukan anggota organisasi. Ini harus diajarkan kepada anggota termasuk anggota baru sebagai cara yang benar untuk menilai, berpikir dan merasakan masalah yang dihadapi (Manggis et al, 2018). Pemaksaan suatu budaya dapat menimbulkan ketidaksesuaian antara karyawan dengan organisasi sehingga mempengaruhi kondisi psikologis karyawan yang merasa tidak nyaman dalam bekerja sama (Piantara et al, 2021).…”
Section: Budaya Organisasiunclassified
“…Hasil temuan penelitian ini sejalan dengan beberapa penelitian sebelumnya pertama, sebuah penelitian yang mengajukan hipotesis menemukan bahwa pengembangan karir berpengaruh positif dan signifikan berdampak pada kinerja karyawan. Artinya semakin tinggi pengembangan karir maka semakin tinggi kinerja karyawan dan jika semakin rendah pengembangan karir, semakin rendah karyawan tersebut kinerja (Manggis et al, 2018). Temuan ini makin memperjelas bahwa pengembangan sumberdaya manusia pada dasarnya adalah berkaitan dengan upaya untuk merekrut, menyeleksi, menempatkan, melatih dan mengembangkan dan memanfaatkan mereka sesuai dengan kebutuhan yang diperlukan.…”
Section: Pembahasanunclassified